THE IMPACT OF CUSTOMER RELATIONSHIP MANAGEMENT ON PATIENT LOYALTY THROUGH PATIENT SATISFACTION AT PERKEBUNAN JEMBER CLINIC - Rachmawati, Fitria Dwi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to investigate the impact of Customer Relationship Management (CRM) on patient loyalty through patient satisfaction at Perkebunan Jember Clinic. In an increasingly competitive healthcare environment, understanding the factors that influence patient loyalty is crucial for hospitals striving to enhance service quality and patient retention. The research identifies CRM as a strategic approach that facilitates effective communication and relationship-building with patients, ultimately leading to higher levels of satisfaction and loyalty. Method: The study employs a quantitative methodology, utilizing surveys to gather data from patients at the clinic. Key dimensions of CRM, such as personalized communication, data management, and service quality, are examined to assess their relationship with patient satisfaction. Results: The findings reveal that effective CRM practices significantly enhance patient satisfaction, which in turn fosters loyalty. Novelty: This research contributes to the existing literature by demonstrating the importance of CRM in the healthcare sector, particularly in promoting patient engagement and loyalty. The results suggest that hospitals implementing robust CRM strategies can achieve better patient retention and improved service delivery. Ultimately, this study serves as a valuable resource for healthcare managers and policymakers aiming to optimize patient relationships and strengthen organizational performance.